Characterizing bioaerosols in PM2.5 in a semi-arid region experiencing desert dust events - Karimi, Hossein; Nikaeen, Mahnaz; Shamsizadeh, Zahra; Hajizadeh, Yaghoub (Frontiers in Environmental Science, 2024)
Fine particulate matter (PM2.5) pollution is a global public health concern, particularly in arid and semi-arid regions that experience dust events. Exposure to PM2.5 has been associated with various short-and long-term health effects, which can be attributed to the composition of the fine particles.This study aimed to assess the concentration of bacteria and fungi in PM2.5 in the air of Isfahan, Iran which experiences air pollution. A total of thirty-nine PM2.5 samples were collected over one year. Bacterial and fungal concentrations associated with PM2.5 were measured using both culturebased method and real-time polymerase chain reaction (PCR). The average concentration of PM2.5 was found to be 56 µg m -3 , with many samples exceeding the recommended limit of 15 µg m -3 set by the World Health Organization for PM2.5 in ambient air. The mean culturable bacterial and fungal concentrations were 39 and 4 CFU m -3 , respectively which showed a significant difference compared to the results obtained through real-time PCR. No significant correlation was found between the levels of bacterial and fungal cells and PM2.5 concentrations. The dominant phyla found in PM2.5 were Firmicutes and Actinobacteria, while Proteobacteria as Gram-negative bacteria were rarely detected. The findings suggest that the climate conditions in Isfahan, characterized by its semi-arid nature with low humidity content, influences the activity and viability of microbial populations, resulting in low concentrations of bioaerosols in PM2.5. Furthermore, it seems that desert dust events don't contribute to increasing the potential health risks associated with bacterial and fungal bioaerosols in PM2.5.